Organizations, disinformation and informational resilience: a critical reflection (Comunicação & Inovação, 2024)
This study deals with disinformation in organizational contexts, from the perspective of informational resilience. A critical reflection is developed to analyze the elements that interfere in the communication process aimed at confronting disinformation, mainly due to the dissemination of fake news in different sociability spaces, including organizations. An exploratory and bibliographical study, it reinforces the importance of understanding that resizing the informational scenario requires collective efforts, and that organizations have an evident social commitment while their existence is directly linked to informational phenomena and their consequences.